IDENTIFICATION OF CALAMANSI FRUIT PEEL ESSENTIAL OIL COMPONENTS FROM BENGKULU USING GC-MS - Yetti Purnama; Kurnia Dewiani; Suci Rahmawati; Linda Yusanti; Novri Fitriani; Merki Aliyadi Sunaryo; Linda Yulyani (Poltekkes Kemenkes Bengkulu, 2022)
Calamansi orange (Citrofortunella microcarpa) is one of the citrus groups that have been cultivated in Bengkulu Province. Calamansi oranges have a distinctive aroma from the volatile oil components found in the skin of the fruit. This study aimed to identify the components of Bengkulu calamansi peel essential oil using GC-MS. The essential oil of calamansi fruit peel was obtained by steam distillation method using vacuum distillation. The essential oil yield obtained was 0.36%. The results of the examination of essential oils using GC-MS showed that there were 6 main compounds. they are 3-carane, Cyclopentanone, 2-(-methyl propyl), Cychexanol, 2methyl-5-(1-methylethenyl), Decanal, L-alpha-Terpineol and D-Crvone.